2017
DOI: 10.21037/jgo.2017.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Advanced duodenal neoplasia and carcinoma in familial adenomatous polyposis: outcomes of surgical management

Abstract: Background: In addition to the presence of neoplasia in the colon and rectum, patients with familial adenomatous polyposis (FAP) may develop numerous polyps and carcinoma within the upper gastrointestinal tract. Methods:The aim of the present paper was to review the incidence advanced duodenal polyposis or cancer and their surgical outcomes. A retrospective review of patients' records from our department was performed. respectively. Duodenal carcinomas occurred later (55.8 years) when compared to advanced aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Two retrospective studies reported that 4 % -6 % of the FAP patients had been surgically treated for duodenal polyposis, describing mortality rates after pancreas-preserving duodenectomy ranging from 5 % to 33 % [105,106]. The in-hospital morbidity was 49 %, without differences between patients with benign adenomatosis and cancer [106].…”
Section: Duodenal Surveillance and Managementmentioning
confidence: 99%
“…Two retrospective studies reported that 4 % -6 % of the FAP patients had been surgically treated for duodenal polyposis, describing mortality rates after pancreas-preserving duodenectomy ranging from 5 % to 33 % [105,106]. The in-hospital morbidity was 49 %, without differences between patients with benign adenomatosis and cancer [106].…”
Section: Duodenal Surveillance and Managementmentioning
confidence: 99%
“…This is the only series that compares FAP related duodenal adenocarcinoma to sporadic duodenal adenocarcinoma (Table 5). 12,19‐28 A previous study which included patients that underwent palliative surgeries and those with metastatic disease with FAP‐associated duodenal cancer noted a median survival of 11 months 26 . While that is still probably true, we noted an overall median survival of 7.4 years in patients who underwent surgery with curative intent.…”
Section: Discussionmentioning
confidence: 51%
“…In fact, the surveillance should start after 25 years of age. When necessary, radical procedure such as PD may be performed with acceptable morbidity by skilled surgical teams (29).…”
Section: Discussionmentioning
confidence: 99%